LITERATURE REVIEW : TERAPI NON FARMAKOLOGI PADA KLIEN POST OPERASI HERNIOTOMI DENGAN NYERI AKUT - Luh Condrosasi (Viva Medika, 2020)
Background: Hernia is an emergency condition that requires immediate treatment by performing surgery in the form of a herniotomy surgery. An incision during a herniotomy can cause tissue damage, which can lead to postoperative pain or surgery. Purpose: The purpose of this review literature is to analyze what non-pharmacological therapies can be used to treat post herniotomy surgery pain. Method: This study explores quantitative evidence or the results of 11 scientific journals published in an electronic database in the form of Google Scholar by including three keywords in the form of "non pharmacological therapy", "post herniotomy surgery" and "acute pain" and is limited to the range of 2011- 2020. Results: The results of 11 research journals that have been reviewed there are several non-pharmacological therapies that can be used to reduce pain intensity in herniotomy postoperative patients, including distraction techniques in the form of classical music therapy and listening therapy to read the Qur'an (murrotal therapy), hand-held therapy fingers, deep breathing relaxation techniques, the merging of SEFT (Spiritual Emotional Freedom Technique) therapy and listening therapy to the reading of the Qur'an (murrotal therapy) as well as a combination of deep breathing relaxation and early mobilization. Conclusion: After being given non-pharmacological therapy the intensity of the respondent's pain decreased and the respondent appeared to be calmer and relaxed. Keywords: non pharmacological therapy, post herniotomy surgery, acute pain.